General equilibrium with banks and the factor-intensity condition - Leão, E. (2012)
This paper looks at the role played by the factor-intensity condition in the model developed by Leao (2003). To do this, we examine how the model reacts when the factor-intensity condition is reversed so that the banking industry ceases to be the capital intensive sector and becomes the labour intensive sector. Simulation results show that, in general, the qualitative nature of the results does not change. However, there two cases where the qualitative results are affected: the response of the real wage and of the labour supply to a shock in the banks technological parameter. We present an interpretation for these results based in part on the framework devised by Heckscher and Ohlin. We conclude that the factor-intensity condition does play a significant role in the model of Leao (2003).